Neuro-fuzzy based joint relay-selection and resource-allocation for cooperative networks - Kaiser, M. Shamim; Shah, Raza Ali; Ahmed, Kazi M. (© 2011 Transactions on Electrical Engineering, Electronics, and Communications, 2016)
This article was published in Transactions on Electrical Engineering, Electronics, and Communications [© 2011] The Journal's website is at: http://www.ecti-thailand.org/assets/papers/1096_pub_34.pdf